2011
DOI: 10.1111/j.1444-0938.2011.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corneal astigmatism, corneal curvature and meridional differences on corneal hysteresis and corneal resistance factor

Abstract: Background: This study investigated the influence of corneal astigmatism, corneal curvature and meridional differences on corneal hysteresis (CH) and the corneal resistance factor (CRF) in a group of normal Chinese persons. Methods: Ninety-five participants were recruited and data from the eye with higher corneal astigmatism were analysed. The anterior corneal curvature was measured by corneal topography. The Goldmann-correlated intraocular pressure (IOPg), cornealcompensated intraocular pressure (IOPcc), CH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
3
1
Order By: Relevance
“…Previous studies have reported that corneal toricity did not affect CH and CRF measurements . Despite the significant difference in corneal toricity between the two refractive groups, no association was observed between corneal stiffness and toricity.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have reported that corneal toricity did not affect CH and CRF measurements . Despite the significant difference in corneal toricity between the two refractive groups, no association was observed between corneal stiffness and toricity.…”
Section: Discussioncontrasting
confidence: 54%
“…However, no correlation between corneal astigmatism and viscoelastic properties was found in this study and these results are in line with previous findings [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Kamiya et al reported similar result; they did not find any correlation between mean K value and CH and CRF in 86 eyes of 43 patients with a mean age of 39 years [3]. Wong and Lam found no correlation between mean K and CH and CRF in Chinese adults [9]. However, 2 different studies from Far East reported contradictory results.…”
Section: Discussionmentioning
confidence: 89%
“…Hwang et al found that corneal volume was positively correlated with CH, but not CRF [20]. Wong and Lam reported positive correlation both with CH and CRF [9]. In a recent study both CH and CRF were found to be correlated positively with CC and CV for the normal, keratoconic, and crosslinked eyes [22].…”
Section: Discussionmentioning
confidence: 99%